Manejo racional eleva o bem-estar de bovinos Guzerá e melhora a eficiência do trabalho de vacinação - Neto, Marcos Chiquitelli [UNESP]; Titto, Cristiane Gonçalves; Filho, José Nicolau Próspero Puoli [UNESP]; Longo, Ana Luisa Silva; Da Cunha Leme-Dos-Santos, Thays Mayra; Titto, Evaldo Antonio Lencioni; Camerro, Leandro Zuccherato [UNESP]; Pereira, Alfredo Manuel Franco (Malque Publishing, 2015)
The experiment was done in the Teaching, Research and Extension Farm (FEPE-UNESP/Ilha Solteira). One hundred and twenty Guzerat cattle of different ages were used in the study: 40 mature cows, 40 yearling steers and 40 calves. Twenty animals of each category were vaccinated by rational management and the other 20 by conventional method. For calves, when they were submitted to rational management during the vaccination process, the management efficiency indicators showed lower averages, with lower time of work execution (P <0.001), repetitive introduction of the needle and bleeding at the injection site (P <0.05); as well as on the behaviors like reacting to the introduction of needle (P <0.01), body movement (P <0.001), jump up on another animal and attempting to or/jumping out of chute (P <0.05). In the category of mature cows, the rational management also resulted in lower values of vaccine losses (P <0.05), bleeding at the injection site, time of work execution and application of the vaccine in the wrong location (P <0.001), as well as some behaviors like reacting to the introduction of needle (P <0.01) and body movement (P <0.001). Similarly, the results obtained for yearling steers also showed significant differences between the two types of management used, with lowest average in the rational management on the indicators such as time of work execution and application of the vaccine in the wrong location (P <0.001), and behaviors such as body movement (P<0.01) and attempting to escape/jumping out of the chute (P <0.05). In this context, it is noted that the conventional management of vaccination possibly caused a sense of threat in animals, emphasizing fear and escape reactions, making the routine management more difficult, causing loss material and quality loss in the final product (beef), and increase the risk of accidents due to more aggressive behaviour toward the operator.
Rational management raises the Guzerat cattle welfare and improves the efficiency of vaccination work
Keywords: Aversive Behavior; Beef Cattle; Corral; Stress